1994
DOI: 10.1097/00132586-199410000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Sufentanil and Alfentanil Cause Vasorelaxation by Mechanisms Independent of the Endothelium

Abstract: 1. The aim of these experiments was to determine if the vasorelaxation of the rat isolated aorta induced by sufentanil or alfentanil is mediated by the endothelium, and, if not, by a-adrenoceptor blockade, or a direct effect on the smooth muscle.2. Both sufentanil (from 10-7 mol/ L to 10-4 mol/ L) and alfentanil (from 10-7 mol/ L to 3 x 10-4 mol/ L) relaxed rings, where endothelium was intact and precontracted with 40 mmol/ L KCl, in a concentration-related manner. Similarly, sufentanil and alfentanil relaxed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
(5 reference statements)
1
3
0
Order By: Relevance
“…Sufentanil could induce a decrease in the smooth vascular tonicity by acting directly on the vascular smooth muscle and making vasorelaxation easier. These results are in agreement with those of Karasawa and colleagues [36], who found that fentanyl induces vasodilation via a direct action on muscular smooth cell and by locking alpha-adrenergic receptors. However, because in our study these changes were observed during the injection of a combination of midazolam and sufentanil, we cannot determine whether sufentanil was, by itself, responsible for the decrease in vascular tonicity or only reinforced an effect started under midazolam.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Sufentanil could induce a decrease in the smooth vascular tonicity by acting directly on the vascular smooth muscle and making vasorelaxation easier. These results are in agreement with those of Karasawa and colleagues [36], who found that fentanyl induces vasodilation via a direct action on muscular smooth cell and by locking alpha-adrenergic receptors. However, because in our study these changes were observed during the injection of a combination of midazolam and sufentanil, we cannot determine whether sufentanil was, by itself, responsible for the decrease in vascular tonicity or only reinforced an effect started under midazolam.…”
Section: Discussionsupporting
confidence: 93%
“…Sufentanil has been shown to decrease peripheral vascular resistances through a direct vascular effect [35]. Karasawa and colleagues [36] showed this effect to be due to an endothelium-independent vasorelaxation mediated by both an alpha-receptor blockage and a direct effect on smooth muscle. In addition, Stefano and colleagues [37] reported that endothelial cells contain opiate receptors called mu3 which are coupled to NO release and vasodilation.…”
Section: Discussionmentioning
confidence: 99%
“…In vein strips precontracted with 5-HT at 37°C, a dose-dependent vasodilation was observed with fentanyl, remifentanil and sufentanil. The direct effects of opioids such as fentanyl, remifentanil and sufentanil on blood vessels have been studied extensively under normal temperature conditions [4,5,15] . These effects can be mediated by either alterations in autonomic nervous system activity or by direct actions on blood vessels [14].…”
Section: Discussionmentioning
confidence: 99%
“…These effects can be mediated by either alterations in autonomic nervous system activity or by direct actions on blood vessels [14]. The direct effects of opioids such as fentanyl, remifentanil and sufentanil on blood vessels have been studied extensively under normal temperature conditions [4,5,15] . In previous study, we also showed that fentanyl and remifentanil produces significant dose-dependent vasodilation starting at clinically relevant concentrations and the maximal relaxant effect of fentanyl was significantly higher than remifentanil in human saphenous vein [16].…”
Section: Discussionmentioning
confidence: 99%